Hermenêutica gestáltica do abuso sexual para uma adolescente - ARAÚJO, Lucivaldo da Silva (Universidade Federal do Pará, 2011)
This qualitative research of orientation Phenomenology, existential gestalt, tries to reveal some meanings attributed to the phenomenon of the abuse sexual inside family, through a case study in that the informer, of the 9 to the 11 years, were been victim for the father and still today, in her existential field, she is influenced by the existence of that experience. The violence against the child, in their several modalities, is a problem of public health and of relationships between family and who takes care the child. In if treating of the sexual abuse, in that the aggressor is the responsible for the primary cares, usually, there is denial for the victim, aggressor and the family, and almost always, it happens, involving more than a violence modality. Same not having a consensus among the authors, it is puts in prominence the noxious effects of those events on the health psychic, occupational, physics and the victims' of the development. The data were collected in ONG Republica of Emaús including reading of documents, informal reports, participant observation and interview with the adolescent, being this last one, the main appreciation source. The analysis of the interview conjugated, insofar as possible, the theory of the interpretation of Ricoeur, some concepts of the gestalt-therapy as the one of contact, illustration-bottom, and psychological nutrition and of the Occupational Therapy, as areas, components and the performance contexts. Of the interview were created units of significance that orientated the reflections concerning the meanings of the adolescent's speech. Some results are: presentation of the weight of the existence of the sexual abuse some times as evidence sometimes as bottom; repercussions owncontact without functionality and contact with the other; in the own-image, selfesteem and in some acting areas: learning and socialization. The creative adjustment can be identified in the opening in revealing the experience, what suggests expansion of their contact borders. A conclusion that the study reach, was about the adolescent's relationship with the father that still, she stands out while an open gestalt.